India cardiology training curriculum- a critical reappraisal: Is it the time to rethink? - Aditya Kapoor; Rishi Sethi; Rakesh Yadav (Indian Heart Journal)
The challenges and rigors of the modern-day health care systems demand a critical reappraisal of our training paradigms in cardiology. Today, modern day DM and DNB Cardiology training needs to seamlessly amalgamate traditional teaching methodologies with the rapidly evolving technology based educational tools now available to us for personalized and adaptive learning. The contemporary cardiology curricula need to incorporate ALL components of clinical competency including cognitive, psychomotor and affective skills to enable the next generation of cardiologists to provide truly holistic care to their patients. In addition, a greater focus on impactful cardiology research with an intent to publish it while in training, is likely to encourage at least some of the young trainees to pursue careers in academia. Most importantly, the exit examination patterns need to be restructured. We need to decide whether we need cardiologists who simply follow textbooks and are trained in procedures —or we need those who have the ability to themselves write the next chapters in cardiology, have the precision of thought, the depth of empathy, and the courage to question.